Abrindo espaços para formação de educadores ambientais numa abordagem transdisciplinar: a vivência do NUPEAT - Andrade, Lívia Costa de (2012)
This paper aims to discuss the need for ever more imminent training of environmental educators aware and didactically well prepared to contribute to the disruption of this paradigm separative we live in today, in search of a unified paradigm, based on transdisciplinarity and the theory of complexity. To do so, drew a dialogue between researchers from different disciplines, to articulate ideas and proposals for realization of these educators may have a solid foundation in their academic training, aiming to transform itself into agents of educational transformation and social consequence. Has sought to deepen the Transdisciplinary approach, the Culture of Peace and Human Values to bring consistency to give theoretical support for the survey.This study was conducted through qualitative research methodology, based on documentary research, participant observation and the technique of focus groups and interviews. The research took place at the Center for Studies and Research in Environmental Education and the Institute of Transdisciplinary Environmental Studies Associate of the Federal University of Goiás and Universidade Salgado de Oliveira Campus Goiânia.